Retrospective assessment of acute poisoning incidents by pharmaceutical agents in Jordan: Data from Pharmacy One™ Poison Call Center, 2014 to 2018—Part II. Issue 2 (17th April 2020) - Yehya, Alaa; Albals, Dima; Issa, Reem; Fawadleh, Aida
Abstract: Poison control centers provide surveillance data that can be used to estimate the magnitude of poisoning cases and the level of public awareness and to evaluate control measures. The aim of this study is to describe the drug‐related poisoning queries received by the Pharmacy One™ Poisoning Call Center (P 1 PCC) in Jordan. This is a retrospective descriptive study of the acute drug‐related poisoning incidents in the Jordanian population recorded by the P 1 PCC during the 2014‐2018 period. The inquiries received were recorded on a predesigned form. The demographic data, including the age and the sex of the patient, the route of and reason for exposure and the drug therapeutic groups, in addition to medical outcomes, were extracted utilizing computerized Oracle and Excel spreadsheets. During the period of evaluation, 900 drug‐related poisoning incidents were reported to the P 1 PCC. The majority of calls (48.5%) were received via 911, followed by the public (48.56%) and healthcare professionals (27.1%). More than half of the poisoning incidents were recorded among males (52.5%). Adults were the most affected group (40.5%), followed by children (34.0%). Unintentional exposure was the most common cause of poisoning (58.6%), followed by suicide attempts (25.3%). Nonsteroidal anti‐inflammatory drugs and paracetamol caused the majority of the reported cases. Poisoning incidents were mainly classified as mild to moderate (56.1%), while only 16.6% were severe. The P 1 PCC has demonstrated an important and vital role in improving patient safety and providing education on rational drug use. Reflections on these data can be used to increase public awareness in promoting the rational use of medications among Jordanian citizens.